How do they create 'Superpower'? An exploration of knowledge-creation processes and work environments in the wearable technology industry. Issue 1 (2nd January 2016) - Raj, Deepika; Ha-Brookshire, Jung E
ABSTRACT: Wearable technology (WT) offers tremendous opportunities for growth and innovation for many of today's businesses. It presents unique challenges in organising heterogeneous productive teams from multi-disciplines. However, little is known about how these WT firms operate to facilitate innovations. Therefore, this study explored the meaning of successful WT, the knowledge-creation processes, and the work environments described by WT professionals in the USA and the Netherlands. An interpretive analysis of 16 in-depth interviews revealed that, a successful WT makes life easier by 'making you do more with less', and solving multiple problems, that gives 'super power' to human beings. The findings were mostly consistent with the organisational knowledge creation theory in that knowledge is created through socialisation by personal communication, internalisation of knowledge by experimentation, and combination by learning from and teaching other members of WT communities. A productive WT work environment was explained to be respectful and nurturing.